Economic study to predict wheat production in Libya for the period (2018-2026) - Mohamed O. Elshwerf; Albibas, Najah (Journal of Pure & Applied Sciences, 2018)
The objective of the research is to predict the quantities produced from wheat in Libya for the period 2018-2026. In order to reach this goal, the descriptive approach was used by listing information about the research variables. The analytical method of applying different statistical prediction methods Wheat production in Libya, and it was found that the Moving Average model is the ARIMA (0,1,12) model, as well as the Holt model. The results of the comparison between the two models showed that the Holt method is the best in predicting wheat production in Libya, During which about 162.89 thousand tons during the year 2026.